Observing Religious Harmony Through Strengthening Religious Moderation And Religious Acceptance In The Catholic Community In Bitung City, North Sulawesi Province - Marthinus Marcel Lintong (Green Publisher Indonesia, 2024)
This study aims to find out how much the strengthening of religious moderation and religious Acceptance have influenced religious harmony in the Catholic community in Bitung City, North Sulawesi Province. The method used in this study is a quantitative research method with a correlative approach because it aims to test hypotheses regarding the magnitude of the influence and whether or not there is a relationship between various variables. The sample in this study was sought using the Slovin formula, and the results of the research sample were 95 people. The research instrument used was to distribute questionnaires with alternative answers that depended on the form of statements based on the Likert scale